Imidazolium-based catenane host for bromide recognition in aqueous media. Issue 1 (18th December 2020) - Serpell, Christopher J.; Park, Ah Young; Robinson, Carol V.; Beer, Paul D.
Abstract : A tetracationic imidazolium-based catenane is reported which is selective for bromide over other halides in aqueous media. Abstract : The synthesis of a novel catenated system which is dense in cationic hydrogen bonding imidazolium units is described. The interlocked host system displays a preference for binding of bromide over other halides, overcoming basicity and Hofmeister trends, under aqueous conditions. This is the first example of an imidazolium-based catenane acting as an anion host through C– H hydrogen bonding.